Development of an FPGA-based gate signal generator for a multilevel inverter - Salim, F.; Azli, N. Ahmad (2003)

(untitled)
The application of Field Programmable Gate Array (FPGA) in the development of power electronics circuits control scheme has drawn much attention lately due to its shorter design cycle, lower cost and higher density. This paper presents an FPGA-based gate signal generator for a multilevel inverter employing an online optimal PWM switching strategy to control its output voltage. FPGA is chosen for the hardware implementation of the switching strategy mainly due to its high computation speed that can ensure the accuracy of the instants that gating signals are generated. The gate signal generator has been realized by an FPGA (FLEXlOKZO) from Altera. The design and development of the FPGA based gate signal generator is described in detail. Results from the timing simulation using MAX+PLUSII software are given and verified by the results obtained from the FLEXlOK2O output.